2002
DOI: 10.1046/j.1469-8137.2002.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent growth rate determines changes in the population of Planktothrix rubescens over the annual cycle in Lake Zürich, Switzerland

Abstract: Summary• Analyses were made to determine which changes in a Lake Zürich population of Planktothrix rubescens were dependent on light-and temperature-dependent growth rates, and when growth was limited by the mixing depth.• Changes in vertical distribution of the cyanobacterium, determined weekly from August 1998 to September 1999, were related to growth increments calculated at 1-h time and 1-m depth intervals from values of irradiance, attenuance, temperature and biomass in the lake, using algorithms based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
138
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 38 publications
13
138
0
Order By: Relevance
“…5) notably coincides well with the observations in Lake Bourget (Jacquet et al, , 2014bLe Vu et al, 2011). In reality, this phenomena is usually attributed to buoyancy regulation (Walsby et al, 2004), whereas in this study, no active mobility mechanism has been considered and their sub-surface growth largely re ects the parameterized low-light tolerance and high-light inhibition of the species (Walsby and Schanz, 2002). The depth-dependent mortality we assumed for P. rubescens (eq.14) does not play a signi cant role in the occurrence of such thin layers, whereas it certainly pulls the depth of maximum concentration a few meters upwards.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…5) notably coincides well with the observations in Lake Bourget (Jacquet et al, , 2014bLe Vu et al, 2011). In reality, this phenomena is usually attributed to buoyancy regulation (Walsby et al, 2004), whereas in this study, no active mobility mechanism has been considered and their sub-surface growth largely re ects the parameterized low-light tolerance and high-light inhibition of the species (Walsby and Schanz, 2002). The depth-dependent mortality we assumed for P. rubescens (eq.14) does not play a signi cant role in the occurrence of such thin layers, whereas it certainly pulls the depth of maximum concentration a few meters upwards.…”
Section: Discussionmentioning
confidence: 95%
“…P. rubescens was assigned as a separate algal group because of its distinctive eco-physiology characterized by low-light tolerance (Walsby and Schanz, 2002), slow growth (Bright and Walsby, 2000), and grazing defense (Kurmayer and Jüttner, 1999) as well as the fact that it represented about half of the phytoplankton assemblage in some years ( Fig. 1,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of P. rubescens during the summer months is partly due to its ability to form strong thickening in the metalimnetic layers provided that the light intensity is not below the Lim. 49 (2013) 309-318compensation point (Walsby and Schanz, 2002). The control of the vertical position is associated with the action of gas vesicles, cellular structures providing positive buoyancy (D'Alelio et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among cyanobacteria proliferating in temperate areas, Planktothrix rubescens is characterized by its localization in the metalimnic layer of the water column of deep lakes. This species is particularly well adapted for growing at low light intensities and also at low temperatures (Oberhaus et al, 2007) and has been found in many prealpine lakes (Walsby and Schanz, 2002;Ernst et al, 2009). In addition, P. rubescens is able to produce microcystins , which are dangerous hepatoxins that threaten both human and animal health Briand et al, 2003).…”
Section: Introductionmentioning
confidence: 99%